The Ash Soap making in the state of Minas Gerais, Brazil: from the status of ethnoscience to its mediation for the classroom using an ethnographic hypermedia system - Paulo César Pinheiro; Marcelo Giordan (Investigações em Ensino de Ciências, 2010)
The ash soap making process developed by women from the interior of the state of Minas Gerais, Brazil, is described and analyzed in order to typify it as ethnoscience. Some of the major conceptions related to folk knowledge, ethnoscience and the chemistry of saponification are presented in order to justify this enterprise. The theoretical and methodological aspects of the ethnographic research carried out with the group of women investigated is discussed and an approximation between the knowledge of these women, the Chemistry knowledge and that of the students of the secondary level is proposed by means of an ethnographic hypermedia as mediational mean for the classroom.